The effects of social-media based social comparison information and similarity mindsets on COVID-19 vaccination uptake cognitions. - Herzog, Noelle K.; Vasireddy, Harika; Drenner, Dylan A.; Rose, Jason P. (Journal of Behavioral Medicine, 2023)
Vaccine hesitancy—delays in vaccine uptake when one is readily available—is an important public health issue. During the COVID-19 pandemic, the role of psychosocial factors in influencing cognitions and behaviors related to vaccine uptake have been examined. Using an online sample of unvaccinated U.S. adults (N = 300), we examined the influence of COVID-19-related social media-based comparison information (e.g., others' attitudes about taking the vaccine)—as well as the moderating impact of (dis)similarity mindsets and indirect influence of affective associations, norm perceptions, and self-evaluations of efficacy—on vaccination uptake intentions. Participants reported higher intentions for vaccine uptake following exposure to cautious comparison models (e.g., those that engaged in health prevention behaviors, intended to get vaccinated) versus risky comparison models (e.g., those who did not engage in health prevention behaviors, did not intend to get vaccinated) and neutral comparison models and this effect was indirect through positive affective associations about taking the vaccine. There were no main or interactive effects of (dis)similarity mindsets. Understanding the psychosocial factors that influence health cognitions and behaviors in the context of an infectious disease pandemic will advance theoretical development and aid in creating interventions targeting vaccine uptake.